Nilai-Nilai Pendidikan Islam pada Tari Zapin di Kampong Zapin Desa Meskom Kecamatan Bengkalis - Robi'ah Robi'ah (STAIN Bengkalis, 2021)
This research was conducted in Meskom Village. This study aims to determine the values of Islamic education contained in the Zapin dance in Meskom village, Bengkalis sub-district, and instill these values in children. This research is field research conducted in the Zapin village of Meskom, Bengkalis district. The subjects in this study were the head of Zapin in the village of Zapin, Bengkalis district, and the object of this study was the values of Islamic education found in Zapin dance. The population taken by the author in this study amounted to the head of the studio. To support the research data, the author uses observation, interview, and documentation techniques, while for data analysis techniques, qualitative descriptive analysis techniques are used. Based on research conducted by the author, the values of Islamic education contained in the Zapin Kampong Zapin dance, Meskom Village, Bengkalis District, have Islamic educational values. It can be seen from the research that educational values have been applied in daily life in Meskom village.